Morphotropic phase boundary and electrical properties of 1-x[Bi 0.5Na0.5]TiO3 -xBa[Zr0.25Ti 0.75]O3 lead-free piezoelectric ceramics - Parija, B.; Badapanda, T.; Rout, S. K.; Cavalcante, L. S. [UNESP]; Panigrahi, S.; Longo, Elson [UNESP]; Batista, N. C.; Sinha, T. P. (Elsevier, 2013)
Lead-free solid solutions (1-x)Bi0.5Na0.5TiO 3 (BNT)-xBaZr0.25Ti0.75O3 (BZT) (x=0, 0.01, 0.03, 0.05, and 0.07) were prepared by the solid state reaction method. X-ray diffraction (XRD) and Rietveld refinement analyses of 1-x(BNT)-x(BZT) solid solution ceramic were employed to study the structure of these systems. A morphotropic phase boundary (MPB) between rhombohedral and cubic structures occured at the composition x=0.05. Raman spectroscopy exhibited a splitting of the (TO3) mode at x=0.05 and confirmed the presence of MPB region. Scanning electron microcopy (SEM) images showed a change in the grain shape with the increase of BZT into the BNT matrix lattice. The temperature dependent dielectric study showed a gradual increase in dielectric constant up to x=0.05 and then decrease with further increase in BZT content. Maximum coercive field, remanent polarization and high piezoelectric constant were observed at x=0.05. Both the structural and electrical properties show that the solid solution has an MPB around x=0.05. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: C. Electrical property; Phase boundaries; Raman spectroscopy; Rietveld refinement; High piezoelectric constant; Lead-free piezoelectric ceramic; Lead-free solid solutions; Morphotropic phase boundaries; Solid solution ceramics; Solid state reaction method; Structural and electrical properties; Temperature dependent; Piezoelectric ceramics; Sodium; Solid solutions; Solid state reactions; X ray diffraction; Electric properties